2011
DOI: 10.1007/s00595-010-4432-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the efficacy of FOLFIRI plus bevacizumab as second-line treatment in metastatic colorectal cancer patients

Abstract: The results of this study suggest that FOLFIRI plus BV is a viable option in second-line treatment for mCRC refractory to first-line FOLFOX (5-fluorouracil, leucovorin, oxaliplatin) alone, and indicate that CA125 might be a predictive biomarker for the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…However, findings from the vatalanib study suggested that there was a trend towards better clinical outcomes in the subgroup of patients with high LDH (Van Cutsem et al , 2011b) and, together with our findings, indicate that high baseline LDH levels may be associated with improved patient outcomes. However, such findings have not been demonstrated in previous studies with bevacizumab (Suenaga et al , 2011; Scartozzi et al , 2012; Cetin et al , 2012). These inconsistencies may indicate that, rather than overall LDH expression, levels of specific isoforms of LDH may have a predictive influence on clinical outcomes.…”
Section: Discussioncontrasting
confidence: 69%
“…However, findings from the vatalanib study suggested that there was a trend towards better clinical outcomes in the subgroup of patients with high LDH (Van Cutsem et al , 2011b) and, together with our findings, indicate that high baseline LDH levels may be associated with improved patient outcomes. However, such findings have not been demonstrated in previous studies with bevacizumab (Suenaga et al , 2011; Scartozzi et al , 2012; Cetin et al , 2012). These inconsistencies may indicate that, rather than overall LDH expression, levels of specific isoforms of LDH may have a predictive influence on clinical outcomes.…”
Section: Discussioncontrasting
confidence: 69%
“…Increased toxicity is not unexpected when biologics are added to combination therapy [4,10,13,18,[20][21][22][23]. Indeed, the addition of cetuximab to irinotecan in second line enhanced chemotherapy-related toxicities in terms of diarrhoea (28.4% versus 15.7%), fatigue (7.7% versus 3.3%) or neutropenia (31.8% versus 25.4%) [12].…”
Section: Discussionmentioning
confidence: 95%
“…In many, if not all the clinical trials combining BV into 2nd-line chemotherapy for patients with mCRC, the standard dosage was either 5 mg/kg on day 1 per 2-week cycle or 7.5 mg/kg on day 1 per 3-week cycle. [ 5 , 6 , 8 , 9 ] In ECOG E3200 trial, the investigator used even higher dosage of BV, 10 mg/kg on day 1 every 2 weeks, to achieve improved OS of 12.9 months, and PFS of 7.3 months. [ 9 ] Unlike previous studies, in the current study, the dosage of BV used was 2.5 mg/kg on day 1 per 2-week cycle, only the half of regularly used dosage in other studies, or even the quarter of the dosage of BV in ECOG 3200 trial.…”
Section: Discussionmentioning
confidence: 99%